(untitled) (Philologia, 2021)
This paper discusses attitudes towards the varieties of the Serbian language. The research included 88 subjects (41 ale and 47 female). Subjects were university students selected from all levels of study, from 18 different faculties and from 49 different towns. Subjects think that the standard variety of Serbian is better than its dialects, but they also support parallel use of bith, depending on the situation. Town speech is better evaluated than village speech for its nuances, but generally speaking, it can be concluded that they hold equal status.